Respostas
respondido por:
1
Resposta:
. 31° 47' 39"
Explicação passo-a-passo:
.
. 47° 36' 25" - 15° 48' 46" (1' = 60")
. = 47° 35' 85" - 15° 48' 46"
. = 47° 35' 39" - 15° 48' 00" (1° = 60')
. = 46° 95' 39" - 15° 48' 00"
. = 31° 47' 39"
.
(Espero ter colaborado)
respondido por:
1
Explicação passo-a-passo:
Não é possível subtrair 46" de 25"
• 1° = 60'
• 1' = 60"
Assim:
47° 36' 25" = 46° + 1° + 36' + 25"
47° 36' 25" = 46° + 60' + 36' + 25"
47° 36' 25" = 46° + 96' + 25"
47° 36' 25" = 46° + 95' + 1' + 25"
47° 36' 25" = 46° + 95' + 60" + 25"
47° 36' 25" = 46° 95' 85"
Subtraindo:
46° 9⁸ 5¹⁵' 8⁷ 5¹⁵"
- 15° 4 8' 4 6"
————————
31° 4 7' 3 9"
O resultado é 31° 47' 39"
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás